Breastfeeding Practice among HIV Positive Mothers Receiving Care for PMTCT at the University of Port Harcourt Teaching Hospital (UPTH), Port Harcourt, Nigeria - Nsirimobu Ichendu Paul; Balafama Abinye Alex-Hart (Archives of Current Research International, 2020)
Background: Exclusive Breastfeeding (EBF) is the recommended feeding method for HIV exposed infants in resource limited settings. This study aimed to evaluate the feeding practices and possible determinants among HIV-positive mothers receiving care for prevention of mother-to-child transmission programme (PMTCT) in Port Harcourt, Nigeria. Methods: This was a cross-sectional study among HIV positive mothers who were receiving care for PMTCT. A structured questionnaire was self-administered to mothers whose babies were at least one year old. Information obtained included the sociodemographic characteristics of the mothers, the choice of feeding practiced by the mothers, reason for the choice of feeding, duration of breastfeeding and reason for breastfeeding. Obtained data was analysed and a p-value of <0.05 was considered statistically significant. Results: A total of 234 mothers participated in the study. Exclusive breastfeeding (EBF) was the predominant type of feeding practiced by the mothers with an EBF rate of 91.4%. Prevention of HIV transmission to the child (85.5%) and the nutritional benefits of the milk (70.9%) were the main underlying reason for the mother’s choice of feeding. One hundred and sixty eight (76.4%) breastfed for 7-12 Months, 156 (70.9%) practiced breastfeeding because of personal choice, while 42 (19.9%) breastfed for fear of HIV status being disclosed. Significantly more of the married mothers exclusively breastfed their children than the unmarried counterparts (X 2 = 23.99, p = 0.0001). Conclusion: Breastfeeding is the commonest feeding practice among HIV positive mother and the EBF rate among these mothers is high and must be encouraged. Regular and consistent use of ART among HIV positive mothers must be encouraged and supported since the desire to prevent MTCT was the commonest motivation for the feeding choice among these mothers.